Hemostatic Changes in Patients with Type 1 Diabetes Mellitus and Diabetic Nephropathy - Markus Z. Raul, Erika V. Grey, Vance L. Hughie (Academic Journal of Clinicians, 2023)
Hemostatic Changes in Patients with Type 1 Diabetes Mellitus and Diabetic Nephropathy